Leadership Behaviours and Goals Achievement in Public Senior Secondary Schools - Saka, Ismaeel (JURNAL AL-TANZIM, 2024)
This study aims to analyze the relationship between leadership behavior and the achievement of educational goals in public high schools in Kwara State, Nigeria. The focus of this research is on the three main elements of leadership behavior, namely the welfare package, the role of supervision, and the communication system, as well as how these elements affect educational outcomes. The research method used is a quantitative approach with a correlational descriptive design. Data were collected through adapted questionnaires and interviews with 368 teachers in various public high schools across 16 local government areas in Kwara State. Data analysis was carried out using descriptive and inferential statistics with Pearson correlation at a significance level of 0.05. The results of the study show that there is a significant relationship between welfare packages, supervisory roles, and communication systems and the achievement of educational goals. An adequate welfare package improves teacher motivation and performance, an effective supervisory role contributes to the quality of teaching, and a good communication system ensures better coordination in achieving school goals. The implications of this study emphasize the importance of holistic integration of these elements in leadership strategies to create a conducive learning environment and achieve optimal educational outcomes. This research also opens up space for further research that considers local contexts, demographic variations, and more diverse research methods to gain a more comprehensive understanding.